EARLY DETECTION IN PREVENTING DRUG CONTROL IN CLASS IIA CIKARANG CORRECTIONAL FACILITY - Nugroho, Muhammad Fadhil Adi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
A crisis is an urgent and unexpected situation that can threaten the integrity and well-being of an organization. In the context of correctional institutions, the risk of a crisis, such as a fire, is ever-present. This research explores the Directorate General of Corrections' response to the fire at Tangerang Class 1 Correctional Facility in 2021, which killed 49 inmates and caused major material losses. The analysis focuses on the crisis communication strategies implemented to address the negative impacts and restore public trust. Through qualitative research methods involving interviews and document studies, and using the theories of Situational Crisis Communication Theory and Image Repair Theory, this study examines the effectiveness of the communication strategies used. The findings show that the Directorate General of Corrections successfully implemented a swift, transparent, and coordinated communication strategy, which included the establishment of a Special Crisis Response Team, the selection of competent spokespersons, and quick clarification of circulating information. However, a major challenge remains in managing the dominant negative perceptions in the media. With a well-planned communication strategy and appropriate training, the agency can be better prepared and responsive in facing future crisis challenges. Keywords: Crisis Communication Strategy; Early Detection; Drug Control